Targeted overexpression of regnase-1 in the aorta prevents aneurysm growth in a murine model of Marfan syndrome. (3rd October 2022) - Noormalal, M; Remes, A; Schmiedel, N; Matzen, A; Hille, S; Bozoglu, T; Wolf, A; Zaradzki, M; Karck, M; Kupatt, C; Frank, D; Frey, N; et al.
Abstract: Background/Introduction: Marfan syndrome is a rare genetic disorder caused by mutations in the fibrillin-1 gene. This markedly affects the cardiovascular system, with patients being at a high risk of aortic aneurysm formation. The main players in the disease progression are matrix-metalloproteinases (MMPs) as well as proinflammatory cytokines, in particular interleukin-6 (IL-6). Regnase-1 is a newly identified endoribonuclease that targets the mRNA of proinflammatory markers. Purpose: We aimed to characterize the role of regnase-1 in Marfan syndrome, particularly the effects of its overexpression on inflammatory parameters and elastin degradation in a well-characterized murine model for the disease. Methods: Regnase-1 expression in aortic tissue was assessed using immunohistochemistry. Aortic smooth muscle cells (SMC) from mgR/mgR (Marfan) mice were transduced with vascular targeted AAV9SLR encoding either regnase-1 or enhanced green fluorescent protein (EGFP) as control. Interferon γ (IFN-γ) served as a proinflammatory stimulus and was added to cell culture medium after transduction. We measured elastin and gelatin degradation and analyzed several inflammatory parameters using real-time qPCR, Western Blot, macrophage migration assay and enzyme-linked immunosorbent assay (ELISA). For in vivo studies, mgR/mgR mice were systemically injected with NP3-tagged AAV9 expressing either regnase-1 or EGFP. 4 weeks after injection, aortic diameter was measured using echocardiography. Thoracic aorta and blood samples were taken for further analysis. Results: Immunostaining revealed a marked decrease in regnase-1 levels in the media in aortic tissue of Marfan patients and mgR/mgR mice as compared to controls. AAV-mediated regnase-1 overexpression in vitro decreased elastin degradation and reduced secretion of proinflammatory cytokines, including IL-6, in murine Marfan SMC. It also lowered MMP9 expression and activity as well as NFkB activation. Furthermore, we could prove a marked decline in macrophage migration towards the supernatant of treated SMCs. NP3-tagged AAV9 led to efficient transduction of both aortic endothelial cells and SMC in vivo. Importantly, echocardiographic measurements showed that regnase-1 overexpression significantly reduced aortic diameter at distinct locations. In addition, elastin architecture was markedly improved in the treatment group compared to controls, male mice presented with higher numbers of structural defects. Moreover, our approach led to less expression of MMPs in the media and to lower plasma levels of IL-6 and macrophage chemoattractant protein 1 (MCP-1). Conclusion: Here we show that AAV-mediated regnase-1 overexpression in the aorta ameliorates pathological remodeling in the aortic wall of Marfan mice and could thus potentially prevent progression of aortic aneurysms in Marfan syndrome. We underline, for the first time, a major role of regnase-1 in aortic aneurysm progression in the context of Marfan syndrome. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Deutsches Zentrum für Herz-Kreislauf-Forschung (Oliver Müller)